2012
DOI: 10.4081/cp.2012.e74
|View full text |Cite
|
Sign up to set email alerts
|

Use of Therapeutic Surfactant Lavage in a Preterm Infant with Massive Pulmonary Hemorrhage

Abstract: We report a case of a premature infant presenting with recurrent pulmonary hemorrhage in which we performed a therapeutic lavage with diluted surfactant after an acute episode of bleeding with severe intractable hypoxemia. Repeated small aliquots of diluted surfactant (10×2 mL) allowed rapid improvement in oxygenation and reduction of required mean airway pressures during high frequency oscillatory ventilation. This observation may suggest that surfactant lavage could be beneficial in massive pulmonary hemorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This condition is characterized by the presence of hemorrhagic fluid from the endotracheal tube, accompanied by a sudden respiratory distress and deterioration of clinical condition (increased parameters or MV therapy is required with 1 h of the occurrence of blood fluid). X-ray imaging suggests involvement of more than two lung lobes [14].…”
Section: Massive Pulmonary Hemorrhagementioning
confidence: 99%
“…This condition is characterized by the presence of hemorrhagic fluid from the endotracheal tube, accompanied by a sudden respiratory distress and deterioration of clinical condition (increased parameters or MV therapy is required with 1 h of the occurrence of blood fluid). X-ray imaging suggests involvement of more than two lung lobes [14].…”
Section: Massive Pulmonary Hemorrhagementioning
confidence: 99%
“…21,22 Pulmonary Hemorrhage Pulmonary hemorrhage and subsequent clinical respiratory deterioration is a phenomenon known to occur in the preterm infant population with RDS, with an incidence in the extremely low-birth-weight (ELBW; birth weight of < 1,000 g) infant population of approximately 10 to 16%. 23 Pulmonary hemorrhage occurs most often in the context of RDS treated with surfactant and concomitant patent ductus arteriosus.…”
Section: Oligohydramniosmentioning
confidence: 99%
“…The onset of pulmonary hemorrhage is often accompanied by deterioration in the clinical status, with worsening lung compliance thought to be due, in part, to surfactant inactivation by blood components. 23 The literature addressing the utility and efficacy of surfactant for pulmonary hemorrhage is limited, though older published case series found that the administration of surfactant following pulmonary hemorrhage improves respiratory status, as measured by oxygenation index (OI) and arterial/alveolar oxygen ratio. 24 A more recently conducted meta-analysis did not identify any RCTs examining the effect of surfactant administration for pulmonary hemorrhage that met inclusion criteria for analysis.…”
Section: Oligohydramniosmentioning
confidence: 99%
See 1 more Smart Citation